THE INFLUENCE OF COMBUSTION PROCESS PARAMETER ON THE FORMATION OF SILICA FROM OIL PALM EMPTY FRUIT BUNCH (OPEFB) - Patthi, Ahmad Farid (IRC, 2021)
Naturally, silica can be found in the form of Crystalline such as sand or flint and quartz instead of amorphous form.